Empoderamiento ciudadano a través de la colaboración y participación ciudadana en el GADM del cantón Rocafuerte período 2022 - Murillo Ganchozo, Jeniffer Elizabeth (2025)
Through collaboration and citizen participation, it is ensured that the opinion and will of a community are part of the decision-making process of local and national authorities. However, this is achieved through the empowerment of citizens regarding their duties and rights. The present research was conducted with the objective of strengthening open government management in the GADM in Rocafuerte canton by determining the level of citizen empowerment that exists through collaboration and citizen participation, considering that open government is a public management model based on principles of transparency, citizen participation, collaboration, and accountability. For this purpose, inductive, deductive, and analytical methods were used, through bibliographic, field, and exploratory descriptive research, with information-gathering techniques such as interviews and surveys, both with GADM authorities and the general public. The research revealed a lack of regulations that strengthen the collaboration and citizen empowerment that government entities should offer. Despite this, it was found that there is a considerable degree of citizen empowerment in the canton; however, there is limited access to certain public information. Additionally, there was a lack of knowledge regarding the forms of citizen collaboration to strengthen empowerment. The final contribution based on the results was an action plan that was implemented using the 5W+1H matrix, defining clear and concrete actions to address the identified problems.